Vulnerabilidade social e qualidade da atenção básica dos municípios brasileiros - Ana Luiza Moreira Pauferro (2018)
The objective of the study was to analyze the association between social vulnerability and the quality of Primary Health Care (PHC) services of the brazilian municipalities. It is a cross-sectional study, involving the use of data from Cycle II of the National Program for Improvement of Access and Quality (PMAQ-AB) and Atlas of Social Vulnerability of Brazilian municipalities. Data from the whole universe of the participating teams, distributed in 5040 municipalities were analyzed. The data were collected in the period from 2013 to 2014. Analyzes of association were made, through logistic regressions, between variables of Basic Attention Quality and social vulnerability. For the quality variables, a municipal typology was created to classify, in low, regular and high, the general quality and also quality dimensions (Municipal Management, Structure, Worker Appreciation, Access and Quality of Attention and Work Process Organization; Access, Use, Participation and User Satisfaction). The social vulnerability variables used were the Social Vulnerability Index (IVS) and its dimensions (Urban Infrastructure, Human Capital and Income and Labor). The results showed that 38.6% of the municipalities were classified as low quality, 57.5% as regular and 3.8% as high quality. Among the municipalities with high quality, approximately 70% have low or very low IVS. In the regression analysis, significant magnitude of association was evidenced, even after adjustments by region, coverage of basic attention and population size, indicating that the lower the social vulnerability of municipalities, the greater the chances of reaching high grades. The dimension of the IVS most associated to quality was Human Capital, which presents indicators of health and education in its composition. The Income and Work dimension presented poor association with Quality. The quality dimension most impacted by the increased vulnerability was "Access and Quality of Care and Work Process Organization". The findings indicate that despite the efforts made towards the qualification of Primary Care in Brazil, a significant situation of inequity remains in the provision of quality services and care, which penalizes the most vulnerable populations